The Difference Between Narrative and Systematic Review Studies: A Letter to the Editor - Ebrahim Piri; AmirAli Jafarnezhadgero (Islamic Azad University, Hamedan Branch, 2024)
In general segmentation, review studies are divided into two groups: narrative reviews and systematic reviews. The research methods for narrative and systematic reviews are completely different. Narrative review articles can be written based on the interests of the researcher, which is one of the weaknesses of this style of review, while systematic review articles have an organized structure and are more reliable. Narrative reviews cover diverse topics such as epidemiological findings, concepts and hypotheses of certain psychiatric diseases, current understandings of specific diseases, psychopharmacology, and treatment guidelines. This reflects the fact that systematic reviews have been rapidly and increasingly replacing traditional narrative (explicit) reviews as the standard platform for providing and updating currently available research findings as confident evidence. Most journals have changed their policy regarding the acceptance of review papers, giving priority to systematic reviews as regular review articles and excluding narrative reviews to provide the best evidence for all basic and clinical questions and further hypotheses. The major advantage of systematic reviews is that they are based on the findings of comprehensive and systematic literature searches across all available resources, minimizing selection bias and avoiding subjective selection.